Molecular Characterization Aminoglycosids Resistance Pseudomonas aeruginosa - Al-Shamari, Rana K.; Al-Khteeb, Sumaya N. (Iraqi Journal of Science, 2022)
Resistance to aminoglycosids is a great problem to therapeutics. Aminoglycoside acetyltransferase producing Pseudomonas aeruginosa have been reported to be important cause of nosocomial infections. The purpose of this study was to determine the occurrence of aminoglycoside acetyltransferase. A total of 200 clinical and environmental samples were collected over period of five months. The P. aeruginosa isolates were confirm their identification, antibiotic susceptibility profile according to vitek2 compact system. The isolates were subjected to polymerase chain reaction (PCR) assays with specific primers for aac (6')-I, aac (6')-Ib, aac (3')-I . Only 32 (16.%) P. aeruginosa isolates were recovered from the samples. in present investigation. Gentamicin seemed to offer more resistance (31.3%) than tobramycin (28.1%), which itself is slightly more resistance than amikacin (25%).In PCR experiments using specific primers for genes. aac(6')-I , and aac(6')-Ib were present in 12 (37.5%) and 15 (46.9%) of the isolates, respectively. While the aac (3')-I were negative among all isolates.